Studiare in Italia. Intercultura e inclusione all'Università - Vaccarelli, Alessandro (La melagrana - Open Access, 2015)
This volume documents a pedagogical research, with an opening to social and geographical sciences, carried out in the University of L'Aquila. In addition, it frames the general scenarios related to the society, to the multicultural city and to the internationalization of the studies.